The Effect of Marketing Mix (Product, Price, Place and Process) on Students' Desire to Recommend Lectures in Tourism Academy of NHI Bandung - Amalia Juliana Monika Intan (Budapest International Research and Critics University, 2020)
The purpose of this study was to determine whether the product, price, place and process partially or simultaneously influence the desirability of students to recommend lectures at the NHI Bandung Tourism Academy. The population and sample in this study were students of the Bandung Tourism Academy. The variables of this research are the variable product (product), price (price), place (place), and process (process) as well as the desire to recommend college. The research method uses an explanatory survey. The data analysis method used is multiple linear regression analysis and using the t test and F test. Research results. Based on the results of multiple linear regression analysis